Peningkatan Administrasi Pembukuan Pada Bank Sampah “Sami Berkah” Kel. Meteseh, Kec. Tembalang , Semarang - Heru Yulianto; Endang Dwi Wwhyuningsih; Dimas Adi Wicaksono; Aniqotunnafiah Aniqotunnafiah; Mabrur Ismail; Muhamad Indra Yudi Setiawan (Universitas 17 Agustus 1945 Semarang, 2024)
Bookkeeping administration is an important aspect in waste bank activities because it has the benefit of recording and carrying out complete and detailed reporting within a certain time period, so that there are no differences in calculations between customers and the Waste Bank management. The importance of bookkeeping administration in managing the Waste Bank (recording the entry and exit of each type of waste managed by the Waste Bank), can help optimize waste management and increase the effectiveness of waste management. Simple bookkeeping (in the form of Socialization) was introduced in the transaction cycle at the Bank Sampah